2000
DOI: 10.1016/s0002-9440(10)65063-8
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Expression of Type IV Collagen Chains in Normal and X-Linked Alport Syndrome Kidneys

Abstract: Alport syndrome is an inherited nephropathy characterized by alterations of the glomerular basement membrane because of mutations in type IV collagen genes. COL4A5 mutations, causing X-linked Alport syndrome, frequently result in the loss of the ␣5 chains of type IV collagen in basement membranes. This is associated with the absence of the ␣3(IV) and ␣4(IV) chains and increased amounts of ␣1(IV) and ␣2(IV) in glomerular basement membranes. The mechanisms resulting in such a configuration are still controversia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 56 publications
1
64
1
2
Order By: Relevance
“…4 It has been shown that in the kidney expression of COL4A3, COL4A4 and COL4A5 genes can be cell-type specific. 36,37 In summary, we observed that familial COL4A2 mutations could lead to a wide spectrum of cerebrovascular disorders, including porencephaly, white matter lesions and possibly aneurysm and cerebellar hypoplasia, which might go undiagnosed because of reduced penetrance and variable expression. Additional risk factors may influence the course of cerebrovascular diseases in families with COL4A2 mutations.…”
Section: Pathogenesis Of Col4a2 Mutationsmentioning
confidence: 81%
“…4 It has been shown that in the kidney expression of COL4A3, COL4A4 and COL4A5 genes can be cell-type specific. 36,37 In summary, we observed that familial COL4A2 mutations could lead to a wide spectrum of cerebrovascular disorders, including porencephaly, white matter lesions and possibly aneurysm and cerebellar hypoplasia, which might go undiagnosed because of reduced penetrance and variable expression. Additional risk factors may influence the course of cerebrovascular diseases in families with COL4A2 mutations.…”
Section: Pathogenesis Of Col4a2 Mutationsmentioning
confidence: 81%
“…ecules comprising ␣3, ␣4, and ␣5 chains. Several studies suggest that ␣3 chain is produced by podocytes and glomerular endothelial cells (10). To further evaluate whether the repair of GBM architecture was caused by de novo synthesis of ␣3 chain by the transplanted podocytes derived from the BM in the COL4A3 Ϫ/Ϫ mice, in situ hybridization for COL4A3 transcript was performed (Fig.…”
Section: Ultrastructural Analysis Reveals That Bmt Repairs Gbm and Pomentioning
confidence: 99%
“…In the X-linked form of the disease, mutations in the COL4A5 gene encoding the ␣5(IV) chain cause the absence of the ␣3, ␣4, and ␣5(IV) chains from the GBM, despite the expression of the ␣3 and ␣4(IV) chains in the podocytes (28,29), and the absence of the ␣5 and ␣6(IV) chains from Bowman's capsule (30 -32). Thus, mutations in the ␣5(IV) chain could either prevent the assembly of ␣3␣4␣5 and (␣5) 2 ␣6 protomers altogether or result in defective protomers that are degraded or cannot self-assemble into networks, causing the loss of the ␣3-␣6(IV) chains.…”
Section: Organization Of Chains Within the ␣3⅐␣4⅐␣5(iv) Network-mentioning
confidence: 99%